Increased phosphorus availability from sewage sludge ashes to maize in a crop rotation with clover. (23rd April 2022) - Wollmann, Iris; Möller, Kurt
Abstract: A recycling of Phosphorus (P) from the human food chain is mandatory to secure the future P supply for food production. However, many available recycled P fertilizers from sewage sludge do not have an adequate P bioavailability and, thus, are not suitable for their application in soils with pH >5.5–6.0, unless being combined with efficient mobilization measures. The aim of the study was to test the P mobilization ability of red clover ( Trifolium pratense L.) from two thermally recycled P fertilizers for a subsequently grown maize. Two sewage sludge ashes (SSA) were investigated in a pot experiment at soil pH 7.5 with red clover differing in its nitrogen (N) supply (added N fertilizer or biological N2 fixation (BNF)), followed by maize ( Zea maize L.). Shoot dry matter of maize was almost doubled when N supply of previous grown clover was covered by BNF, instead of receiving added N fertilizer. Similarly, shoot P removal of maize following clover with BNF was significantly increased. It is suggested that the P mobilization is related to the BNF, and a proton release of N2 fixing clover roots led to the measured decrease in soil pH and thereby increased P availability of the tested fertilizers.